Potential to Inhibit Growth of Atherosclerotic Plaque development through Modulation of Macrophage neopterin /7,8-dihydroneopterin synthesis - Gieseg , S.P; Crone, E.; Flaval, E.A; Amit, Z. (Nature Publishing Group, 2008)
SP Gieseg, EM Crone, EA Flaval, Z Amit.